Deciphering the alteration of MAP2 interactome caused by a schizophrenia-associated phosphorylation - Jiali Lyu; Matthew L MacDonald; Shelby Ruiz; Shinnyi Chou; Jordan Gilardi; Serena C Buchwald; Melanie J Grubisha; Robert A Sweet (Neurobiology of Disease)
Microtubule-associated protein 2 (MAP2) is a crucial regulator of dendritic structure and neuronal function, orchestrating diverse protein interactions within the microtubule network. We have shown MAP2 is hyperphosphorylated at serine 1782 (S1782) in schizophrenia and phosphomimetic mutation of S1782 in mice (MAP2S1782E) is sufficient to impair dendritic architecture. We sought to determine how this hyperphosphorylation affects the MAP2 interactome to provide insights into the disorder's mechanisms. We investigated the MAP2 interactome using co-immunoprecipitation and mass spectrometry in MAP2S1782E and MAP2WT mice. We found that S1782E MAP2 led to a substantial disruption of protein-protein interactions relative to WT MAP2. Reduced interactions with PDZ domain-containing proteins, calmodulin-binding proteins, ribosome proteins, and kinesin proteins may all contribute to dendritic impairments induced by S1782E, and may be linked to schizophrenia pathogenesis. Interestingly, novel gain-of-function interactions with PPM1L and KLHL8 nominated these as regulators of phosphoS1782 MAP2 abundance and potential therapeutic targets in schizophrenia.